Image assessment of cervical dimensions after LLETZ: a prospective observational study. Issue 4 (11th December 2012) - Carcopino, X; Maycock, JA; Mancini, J; Jeffers, M; Farrar, K; Martin, M; Khalid, S; Prendiville, W
<x xml:space="preserve">Abstract</x> Objective To assess the impact of large loop excision of the transformation zone (LLETZ) for cervical intraepithelial neoplasia (CIN) on cervical morphology as assessed by three‐dimensional ultrasound. Design Prospective observational study. Setting University Hospital in Dublin. Population Women with CIN who underwent an LLETZ procedure. Methods All 106 participants had a three‐dimensional transvaginal ultrasound scan (3DTVS) performed immediately before and 6 months after LLETZ. The excised LLETZ specimen dimensions were also recorded. Blind analysis of the images was performed. The volume of the uterus and cervix was documented. Main outcome measures The relationship between the extirpated LLETZ dimensions and subsequent cervical and uterine biometry, as assessed by 3DTVS. Results LLETZ induced a statistically significant reduction in both the length (mean, –0.46 cm; P < 0.001) and the volume (–6.12 cm3; P < 0.001) of the uterus, and in the volume of the cervix (–1.60 cm3; P < 0.001). The volume of the excised specimen had a significant impact on the reduction of the length of the uterus (β, –0.038; P = 0.012), the volume of the uterus (β, –0.791; P = 0.036) and the volume of the cervix (β, –0.121; P = 0.046). The circumference of the excised specimen appeared to have a significant impact on the length (β, –0.016; 95% CI, –0.028 to –0.003; P = 0.013) and volume (β, –0.413; 95% CI, –0.719 to –0.107; P = 0.009) of the uterus 6 months after LLETZ. Conclusions The volume of tissue removed at LLETZ is related to the subsequent cervical volume, as well as the uterine length and volume, 6 months after the procedure.